STRATEGI PENINGKATAN PRODUKTIVITAS DAN PENDAPATAN PETERNAK SAPI PERAH PASCA PMK MELALUI TEKNOLOGI SILASE DAN PEMASARAN PRODUK SUSU DI DESA CARANGWULUNG, WONOSALAM, JOMBANG - Sabdoningrum, Emy Koestanti; Hidanah, Sri; Al Arif, Mohammad Anam; Yudaniayanti, Ira Sari; Hasib, Fatin Fadhilah; Soeharsono, Soeharsono; Rahmawati, Kadek; Rosyada, Zulfi Nur Amrina (Jurnal Abdi Insani, 2024)
Carangwulung Village in Wonosalam District, Jombang Regency, faces challenges in milk production due to the Foot and Mouth Disease (FMD) outbreak. This community service program aims to improve the productivity and income of dairy farmers through the application of silage fodder processing technology and effective milk product marketing strategies. The methodology includes counseling and direct practice on silage making and marketing of dairy products to farmers in Carangwulung village, Wonosalam, Jombang. Participants were taught how to make silage feeds from local materials and broader marketing techniques using social media and online marketplaces. The results show a significant increase in farmers' knowledge and skills regarding silage technology and marketing. Awareness of FMD prevention and management also increased. The application of silage technology successfully improved fodder quality and milk productivity, while marketing strategies helped farmers expand market access and increase product value. In conclusion, this program effectively achieved its goal of enhancing the welfare and food security of dairy farmers in Carangwulung Village. Through the introduced technologies and strategies, farmers are now better prepared to face production and marketing challenges, supporting the sustainability of their farming operations.